Personal Weather Station Monitoring using Arduino and LoRa Technology - Ainor Khaliah Mohd Isa; Syahrulhakimi Mamat Raduan (Journal of Engineering Technology, 2022)
Uncertain weather conditions especially in the Malaysian tropical climate have risen the importance of this study. This study developed a prototype of a weather station monitoring using Arduino and LoRa technology. The prototype consists of a DHT11 temperature and humidity sensor, a rain sensor, a transmitter (Arduino Pro Mini and LoRa SX1278 with antenna), a receiver (ESP32 module and LoRa SX12278 with antenna), and a ThingSpeak web application. The prototype will track and monitor rainfall, temperature, and humidity with sensors alerting the user using the ThinkSpeak application. In the ThingSpeak application, a user can keep track of the data obtained from the weather station. As a result, both the transmitter and receiver work well in a 1-kilometre radius. Thus, implementing LoRa technology in the weather station solves the problem of data transmission over a longer distance. The study is preliminary in using the LoRa technology, LoRa network or gateway can be further used to increase the wireless range and have a low power consumption.